Visual Representation Analysis of Instagram Content @atikoh.s in Support Ganjar Pranowo's 2024 Presidential Campaign - Meydisah Olivia; Ririt Yuniar (Ikatan Sarjana Komunikasi Indonesia, 2025)
Instagram is a strategic tool in the political campaign process and is used massively by political spouses, but is often considered only as a tool for image-building or for certain purposes. Siti Atikoh is one of the figures who uses her personal Instagram to support her husband's political strategy. Thus, this study aims to analyze Siti Atikoh's Instagram content, which represents her involvement in the 2024 Presidential Election campaign process, especially to support Ganjar Pranowo's victory. Stuart's representation theory of Hall with a qualitative descriptive approach and visual communication analysis, with data collection techniques through documentation studies of Instagram posts @atikoh.s in the form of photos showing her involvement in the Ganjar Pranowo campaign process during the campaign period (November 2023 - February 2024). The results are first, Siti Atikoh represents herself as a figure of an active